PIGN encephalopathy: Characterizing the epileptology. Issue 4 (18th February 2022) - Bayat, Allan; de Valles‐Ibáñez, Guillem; Pendziwiat, Manuela; Knaus, Alexej; Alt, Kerstin; Biamino, Elisa; Bley, Annette; Calvert, Sophie; Carney, Patrick; Caro‐Llopis, Alfonso; Ceulemans, Berten; Cousin, Janice; et al.
Abstract: Objective: Epilepsy is common in patients with PIGN diseases due to biallelic variants; however, limited epilepsy phenotyping data have been reported. We describe the epileptology of PIGN encephalopathy. Methods: We recruited patients with epilepsy due to biallelic PIGN variants and obtained clinical data regarding age at seizure onset/offset and semiology, development, medical history, examination, electroencephalogram, neuroimaging, and treatment. Seizure and epilepsy types were classified. Results: Twenty six patients (13 female) from 26 families were identified, with mean age 7 years (range = 1 month to 21 years; three deceased). Abnormal development at seizure onset was present in 25 of 26. Developmental outcome was most frequently profound (14/26) or severe (11/26). Patients presented with focal motor (12/26), unknown onset motor (5/26), focal impaired awareness (1/26), absence (2/26), myoclonic (2/26), myoclonic–atonic (1/26), and generalized tonic–clonic (2/26) seizures. Twenty of 26 were classified as developmental and epileptic encephalopathy (DEE): 55% (11/20) focal DEE, 30% (6/20) generalized DEE, and 15% (3/20) combined DEE. Six had intellectual disability and epilepsy (ID+E): two generalized and four focal epilepsy. Mean age at seizure onset was 13 months (birth to 10 years), with a lower mean onset in DEE (7 months) compared with ID+E (33 months). Patients with DEE had drug‐resistant epilepsy, compared to 4/6 ID+E patients, who were seizure‐free. Hyperkinetic movement disorder occurred in 13 of 26 patients. Twenty‐seven of 34 variants were novel. Variants were truncating ( n = 7), intronic and predicted to affect splicing ( n = 7), and missense or inframe indels ( n = 20, of which 11 were predicted to affect splicing). Seven variants were recurrent, including p.Leu311Trp in 10 unrelated patients, nine with generalized seizures, accounting for nine of the 11 patients in this cohort with generalized seizures. Significance: PIGN encephalopathy is a complex autosomal recessive disorder associated with a wide spectrum of epilepsy phenotypes, typically with substantial profound to severe developmental impairment.